E-Selectin-Overexpressing Mesenchymal Stem Cell Therapy Confers Improved Reperfusion, Repair, and Regeneration in a Murine Critical Limb Ischemia Model - Quiroz, Hallie J.; Valencia, Samantha F.; Shao, Hongwei; Li, Yan; Ortiz, Yulexi Y.; Parikh, Punam P.; Lassance-Soares, Roberta M.; Vazquez-Padron, Roberto I.; Liu, Zhao-Jun; Velazquez, Omaida C. (Frontiers in Cardiovascular Medicine, 2022)
Aims Novel cell-based therapeutic angiogenic treatments for patients with critical limb ischemia may afford limb salvage. Mesenchymal stem cells (MSCs) do not overexpress E-selectin; however, we have previously demonstrated the cell-adhesion molecule's vital role in angiogenesis and wound healing. Thus, we created a viral vector to overexpress E-selectin on MSCs to increase their therapeutic profile. Methods and Results Femoral artery ligation induced hind limb ischemia in mice and intramuscular injections were administered of vehicle or syngeneic donor MSCs, transduced ex vivo with an adeno-associated viral vector to express either GFP+ (MSCGFP) or E-selectin-GFP+ (MSCE−selectin−GFP). Laser Doppler Imaging demonstrated significantly restored reperfusion in MSCE−selectin−GFP-treated mice vs. controls. After 3 weeks, the ischemic limbs in mice treated with MSCE−selectin−GFP had increased footpad blood vessel density, hematoxylin and eosin stain (H&E) ischemic calf muscle sections revealed mitigated muscular atrophy with restored muscle fiber size, and mice were able to run further before exhaustion. PCR array-based gene profiling analysis identified nine upregulated pro-angiogenic/pro-repair genes and downregulated Tumor necrosis factor (TNF) gene in MSCE−selectin−GFP-treated limb tissues, indicating that the therapeutic effect is likely achieved via upregulation of pro-angiogenic cytokines and downregulation of inflammation. Conclusion This innovative cell therapy confers increased limb reperfusion, neovascularization, improved functional recovery, decreased muscle atrophy, and thus offers a potential therapeutic method for future clinical studies.